Cement solidification/stabilization of the toxicants from spent commercial SCR catalyst. Issue 2 (21st September 2020) - He, Chuan; Kong, Fanhai; Bao, Qiang; Zhang, Fajie; Wang, Lele; Ma, Yunlong; Yao, Yan
Abstract: BACKGROUND: The present work focuses on a harmless treatment of hazardous substances in spent commercial selective catalytic reduction (SCR) catalyst by using cement as a binder. The spent V2 O5 ‐WO3 /TiO2 SCR catalysts were ground and mixed with the cement to prepare the solidified products, according to a simple method in this study. The solidified products were subsequently submitted to a characterization process based on inductively coupled plasma mass spectrometry (ICP‐MS), X‐ray diffraction (XRD), X‐ray fluorescence (XRF), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and N2 adsorption–desorption analysis. The leaching characteristics of hazardous substances, such as V, As, Cr and Pb, in solidified products were studied and the effects of mixed ratio between deactivated SCR catalyst and cement on leaching characteristics of hazardous substances were investigated. RESULTS: The experimental results showed that the cement was effective in immobilizing hazardous substances (V, As, Cr and Pb) present in the spent catalyst. When the cement hardened with 50% spent catalyst addition, the solidified products exhibited extremely low leaching concentrations of V, As, Cr and Pb, which are 0.6, 1.3, 2.3 mg L −1 and 16.5 μg L −1, respectively. CONCLUSION: The leaching toxicity of hazardous substances is far lower than that of the National Standard of China and European regulations. The characterization analysis revealed that the active silicate sand hydroxyl compounds play an important role in immobilizing hazardous substances in spent SCR catalyst. The cement solidification method was expected to achieve the harmless treatment on spent SCR catalyst for the first time. © 2020 Society of Chemical Industry (SCI)